Assessing the potential of the European Atlantic sturgeon Acipenser sturio to control bivalve invasions in Europe. Issue 2 (30th May 2016) - Ferreira‐Rodriguez, N.; Gessner, J.; Pardo, I.
Abstract : This pilot study explored the potential of juvenile European Atlantic sturgeon Acipenser sturio to feed on two invasive bivalve species, the Asian clam Corbicula fluminea and the Eurasian zebra mussel Dreissena polymorpha . Preliminary results indicate that native A. sturio were feeding on D. polymorpha at a very limited rate and their potential to prevent the establishment of invasive bivalve species, in new and previously invaded areas, is considered limited.